2003
DOI: 10.1161/01.hyp.0000082814.62655.85
|View full text |Cite
|
Sign up to set email alerts
|

AT 1 Blockade Prevents Glucose-Induced Cardiac Dysfunction in Ventricular Myocytes

Abstract: Abstract-Enhanced tissue angiotensin (Ang) II levels have been reported in diabetes and might lead to cardiac dysfunction through oxidative stress. This study examined the effect of blocking the Ang II type 1 (AT 1 ) receptor on high glucose-induced cardiac contractile dysfunction. Rat ventricular myocytes were maintained in normal-(NG, 5.5 mmol/L) or high-(HG, 25.5 mmol/L) glucose medium for 24 hours. Mechanical and intracellular Ca 2ϩ properties were assessed as peak shortening (PS), time to PS (TPS), time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
155
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 213 publications
(164 citation statements)
references
References 34 publications
9
155
0
Order By: Relevance
“…It acts by impeding the assembly of the p47-phox and p67-phox subunits within the membrane NAD(P)H oxidase complex (56,57). Some of the effects of apocynin treatment are protection of the endothelium from the initiating events of atherosclerosis (57), a reduction of p22-phox mRNA expression and cardiac hypertrophy in aldosterone-infused rats (58), and a prevention of hyperglycemia-induced intracellular ROS elevation and myocyte dysfunction (59). Aponycin has also been shown to reduce oxidative stress in stroke-prone spontaneously hypertensive rats, leading to the suppression of cardiac hypertrophy, inflammation and fibrosis (60).…”
Section: Discussionmentioning
confidence: 99%
“…It acts by impeding the assembly of the p47-phox and p67-phox subunits within the membrane NAD(P)H oxidase complex (56,57). Some of the effects of apocynin treatment are protection of the endothelium from the initiating events of atherosclerosis (57), a reduction of p22-phox mRNA expression and cardiac hypertrophy in aldosterone-infused rats (58), and a prevention of hyperglycemia-induced intracellular ROS elevation and myocyte dysfunction (59). Aponycin has also been shown to reduce oxidative stress in stroke-prone spontaneously hypertensive rats, leading to the suppression of cardiac hypertrophy, inflammation and fibrosis (60).…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier study revealed that angiotensin receptormediated activation of NADPH oxidase plays a role in hyperglycaemia-induced cardiac dysfunction [34]. (Fig.…”
Section: Mechanical Properties Of Cardiomyocytesmentioning
confidence: 99%
“…In brief, isolated cardiomyocytes from WT and MyAkt mice were incubated with tunicamycin (3 lg/ml) at 37°C for 5-6 h. A cohort of WT cardiomyocytes were coincubated with the ER stress inhibitor TUDCA (500 lM), or the antioxidant catalase-PEG (15,000 IU/ml) (36) at the same time with tunicamycin. H 2 O 2 (100 lM) was used as the positive control in the absence or presence of the antioxidant catalase-PEG.…”
Section: Intracellular Rosmentioning
confidence: 99%